Research Paper on Liquidity & Profitability Analysis of the Pharmaceutical Companies of India (International Journal of Scientific Research and Management (IJSRM), 2017)
In the era of liberalization, privatization, and globalization, working capital management an integral part of any business situation. Businesses are nowadays managed with flexibility where the strategic aspects largely depend of the stand of competitors.